Thermal, structural and morphological properties of polypropylene and high density polyethylene polymer composites filled with waste urea formaldehyde - TAŞDEMİR, MÜNİR (My University, 2023)
© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.Polypropylene (PP) and high-density polyethylene (HDPE) are the recyclable and easily processed thermoplastics which are commonly used as cable insulation materials. The improvement of thermal and structural properties of PP and HDPE is very important for aging processes. For this purpose, powdered waste urea–formaldehyde was added to PP and HDPE at 5 wt%, 10 wt%, 20 wt% and 30 wt% ratios. The thermal, structural and morphological properties of the produced samples were observed by using thermogravimetric differential thermal analyser, oxygen induction time tests, fourier transform infrared spectrophotometry, X-ray diffractometer and scanning electron microscopy. By the results of the relevant study, the thermal and oxidative stability of the composites was improved by the incorporation of WUF into the polymer matrices. In conclusion, powdered urea–formaldehyde can be a cost-effective and good filler for PP and HDPE.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; POLİMER BİLİMİ; Temel Bilimler (SCI); POLYMER SCIENCE; CHEMISTRY; Natural Sciences (SCI); Polimerler ve Plastikler; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Polymers and Plastics; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Polypropylene; High density polyethylene; Waste urea formaldehyde; Cable insulation materials; Thermo-oxidation stability; DIFFERENTIAL SCANNING CALORIMETRY; INFRARED-SPECTROSCOPY; MECHANICAL-PROPERTIES; QUANTITATIVE-ANALYSIS; BLENDS; HDPE; NANOCOMPOSITE; STABILITY